Case Report: Carbonic anhydrase inhibitor brinzolamide dramatically improved the morphology and also function of a patient with RS1 mutation - Ren, Yue; Liu, Shu; Rong, Jia; Wang, Di; Diao, Miao; Zhang, Yaqi; Tian, Shimiao; Shang, Mingxin; Song, Chuqiao; Guan, Yan; Wang, Zhuoshi; Pang, Jijing (Frontiers in Pharmacology, 2025)
X-linked retinoschisis (XLRS) is an inherited retinal disease caused by mutations in the RS1 gene, which encodes retinoschisin, a protein essential for maintaining the retinal structure during development. Here, we report the therapeutic evidence in a male patient diagnosed with X-linked retinoschisis (XLRS) before and after topical treatment with a carbonic anhydrase inhibitor (CAI), brinzolamide. XLRS-like typical retinal morphology and visual function before treatment and novel improvements gradually from one to 3 months following treatment were observed; then a recurrence of foveal retinoschisis and decreased retinal function occurred because the use of brinzolamide eye drops was disrupted by months-long recurrent upper respiratory tract infections; eventually retinal improvement after resuming brinzolamide were found again, confirming that brinzolamide eye drops could reduce retinoschisis and improve visual acuity. This individualized “dechallenge–rechallenge” evidence chain provides direct supports for the brinzolamide to be the cause in controlling XLRS progression rather than the natural occurring in the course of the disease itself.